2018
DOI: 10.1002/2017jb014728
|View full text |Cite
|
Sign up to set email alerts
|

Out‐of‐Plane Seismic Reflections Beneath the Pacific and Their Geophysical Implications

Abstract: We detect seismic P wave arrivals that reach the surface from a different horizontal direction than the theoretical back azimuth of the earthquake. Slowness, back azimuth, and traveltime of observed out‐of‐plane signals are measured with array methods in relation to the main phases that travel along the great circle path. This directivity information is used to back trace the wave through a 1‐D velocity model to its scattering or reflection location. The focus of this study lies on out‐of‐plane signals reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…The stacking procedure used in producing vespagrams usually assumes that the energy travels along the great circle path. Because of 3D structures and reflector topography, however, the energy can also travel out of plane (e.g., Schumacher et al, ; Schumacher & Thomas, ). Therefore, we also performed slowness‐back azimuth analyses that allow the detection of out‐of‐plane reflections (e.g., Rost & Thomas, ).…”
Section: Data and Observationsmentioning
confidence: 99%
“…The stacking procedure used in producing vespagrams usually assumes that the energy travels along the great circle path. Because of 3D structures and reflector topography, however, the energy can also travel out of plane (e.g., Schumacher et al, ; Schumacher & Thomas, ). Therefore, we also performed slowness‐back azimuth analyses that allow the detection of out‐of‐plane reflections (e.g., Rost & Thomas, ).…”
Section: Data and Observationsmentioning
confidence: 99%
“…These small residuals lie within the average standard deviation σ, which is representing the uncertainties in measuring the observed slowness (σ=0.0075 s/km) and backazimuth (σ=4°) values of the direct P-waves. To measure these uncertainties and estimate standard deviation, we consider all points that have a variation of up to 10% in beam power with respect to the maximum (white contour line in the polar plot of Figure 4c) as performed also by Schumacher et al (2018).…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been used in global seismology for the detection and location of heterogeneities in the Earth mantle that cause scattering and/or reflection of seismic waves (e.g. Kaneshima, 2009Kaneshima, , 2016Kaneshima & Helffrich, 2003;Rost et al, 2008;Schumacher & Thomas, 2016;Schumacher et al, 2018;Weber and Wicks, 1996;Weber et al, 2015;Wicks and Weber, 1996;Wright, 1972;Wright & Muirhead, 1969).…”
Section: Resultsmentioning
confidence: 99%
“…Ballmer et al. (2016) model the Pacific LLSVP with a combination of MORB and primordial material, which generates a velocity discontinuity at depths consistent with the D" reflector within an LLSVP‐like region (Schumacher et al., 2018). Furthermore, Deschamps et al.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, our thermochemical modeling shows that an increase in bm or a decrease in MgO (and to a smaller degree FeO) would generate large R-values. Ballmer et al (2016) model the Pacific LLSVP with a combination of MORB and primordial material, which generates a velocity discontinuity at depths consistent with the D" reflector within an LLSVP-like region (Schumacher et al, 2018). Furthermore, Deschamps et al (2012) and Vilella et al (2021) show that an increase of bm with an increase of Fe has been suggested to be responsible for the LLSVPs.…”
Section: Tablementioning
confidence: 93%